1953
DOI: 10.1139/v53-015
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Dehydration of Copper Sulphate Pentahydrate at Low Pressures of Water Vapor

Abstract: The rate of dehydration of copper sulphate pentahydrate has been determined over a range of low pressures of water vapor. I t has beer1 found that a s the pressures are increased, the rate a t first drops very rapidly; this drop is followed by a period of marked acceleration, whicli is followed in turn by a gradual decline. Copper sulphate pentahydrate has bee11 found to be similar in this respect t o manganous oxalate dihydrate, which has been hitherto regarded as unique in its behavior. The observed effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
3

Year Published

1955
1955
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
0
5
1
3
Order By: Relevance
“…I t would appear reasonable therefore to give the same interpretation of these curves as has been done for the copper sulphate pentahydrate dehydration (2). Under vacuum, the parent lattice breaks down into a state of monohydrate composition which does not yield a pattern of X-ray diffraction lines.…”
Section: Discussionmentioning
confidence: 73%
“…I t would appear reasonable therefore to give the same interpretation of these curves as has been done for the copper sulphate pentahydrate dehydration (2). Under vacuum, the parent lattice breaks down into a state of monohydrate composition which does not yield a pattern of X-ray diffraction lines.…”
Section: Discussionmentioning
confidence: 73%
“…The rate of dehydration of inanganous oxalate dihydrate a t a series of low pressures of water vapor has been determined by Voliner and Seydel (11) and by Topley and Smith (10). Similar rate determinations for the dehydration of copper sulphate pentahydrate have been made by Frost and Campbell (4), who interpreted these rates in terms of the formation of an~orphous inaterial and its subsequent crystallization. Wheeler (12) and Ford (3) have studied the rates of dehydration of the other salts mentioned and found that all were qualitatively similar in the dependence of rate on the water vapor pressure in the vicinity of the reaction interface.…”
Section: Introductionmentioning
confidence: 82%
“…Mehanizam dehidratacije bakar(II)-sulfat-pentahidrata predmet je brojnih studija u proteklih osamdesetak godina [1][2][3][4]. Rezultati ukazuju da ovaj materijal ima neka jedinstvena termička svojstva.…”
Section: Tga Analizaunclassified
“…Na oko 70 °C proizvod zagrevanja CuSO 4 •5H 2 O je trihidrat, CuSO 4 •3H 2 O. U ovom kristalohidratu, atomi kiseonika iz tri molekula vode i atom kiseonika iz sulfat-jona obrazuju deformisan kvadrat u kome su veze Cu(II) i atoma kiseonika iz molekula vode nešto kraće (0,196 nm). Daljim zagrevanjem, moguće je izvršiti potpunu dehidrataciju i dobiti anhidrovanu so, CuSO 4 , kod koje je Cu(II) vezan za atome kiseonika iz sulfat-jona [1][2][3][4].…”
unclassified